SYSTEMIC LITERATURE REVIEW: NEUROLINGUISTICS IN LANGUAGE PROCESSING IN CHILDREN WITH AUTISM SPECTRUM DISORDER (ASD) - Solo, Lenny; Lustyantie, Ninuk; Chaeruman, Uwes Anis (Universitas PGRI Palembang, 2025)
Neurolinguistic research on language processing in children with autism spectrum disorder (ASD) has progressed markedly in the last ten years. The variability in research methodologies and results frequently hinders the formation of a holistic comprehension of advancements in this domain. This study is to do a comprehensive literature review to summarize and evaluate publication trends, principal subjects, and commonly employed methodologies in neurolinguistic research focused on language processing in children with ASD. This analysis also indicates underexplored research areas and gaps that can inform future investigations. This research used a Systematic Literature Review (SLR) methodology in accordance with PRISMA criteria to examine academic papers from many databases, including Google Scholar and Scopus. The research identifies numerous significant trends, such as heightened focus on lexical and semantic perception impairments, the application of brain imaging technology, and linguistics-based therapies. These findings are anticipated to provide a reference for more targeted future study and facilitate the development of therapies designed to improve language skills in children with ASD.